SPOD analysis of noise-generating Rossiter modes in a slat with and without a bulb seal - Himeno, Fernando H.T.; Souza, Daniel S. [UNESP]; Amaral, Filipe R.; Rodríguez, Daniel; Medeiros, Marcello A.F. (Cambridge University Press (CUP), 2021)
The slat represents an important airframe noise source as it extends over almost the entire aircraft wingspan. Most studies of slat noise consider idealized geometries. However, for practical applications, several elements are installed on its cove, such as bulb seals to avoid direct contact with the main wing surface. Previous investigations of an unswept and untapered MD30P30N airfoil reported that the flow dynamics and the corresponding acoustic noise are very sensitive to the presence and location of the bulb seal. For certain locations a second recirculation bubble is created inside the slat cove and the acoustic narrowband peaks are intensified. The present paper shows that the two-bubble topology promotes the recirculation of turbulence within the slat cove. Spectral proper orthogonal decomposition analysis based on the radiated pressure intensity is used to identify the flow structures responsible for sound generation. Even though the recirculating turbulence is mostly incoherent, it interacts with the coherent Kelvin-Helmholtz vortices in the initial part of the mixing layer. Then, vortex merging and straining lead to the formation of complex vortex clusters. Our results show that the origin and evolution of these clusters are consistent with Rossiter's mechanism responsible for the narrowband peaks. The enhanced recirculation accelerates the cluster evolution leading to wider clusters and lower-frequency Rossiter modes.
Keywords: aeroacoustics; low-dimensional models; vortex interactions